2018
DOI: 10.1111/ans.14293
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and associations of painful neuroma in a contemporary cohort of lower‐limb amputees

Abstract: This study presents a lower incidence of painful post-amputation neuroma to those published in the literature. This may be attributed to improved methodology. The described associations require further investigation into central factors leading to neuroma sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…The stimulation of these two neuromas could reproduce all the subject's symptoms. A cohort study showed that the presence of PLP at a follow-up is significantly associated with the formation of a painful neuroma, 22 which is in line with our observations. There are few random controlled trials that can be used to guide physicians in selecting the optimal treatment for PAP.…”
supporting
confidence: 91%
“…The stimulation of these two neuromas could reproduce all the subject's symptoms. A cohort study showed that the presence of PLP at a follow-up is significantly associated with the formation of a painful neuroma, 22 which is in line with our observations. There are few random controlled trials that can be used to guide physicians in selecting the optimal treatment for PAP.…”
supporting
confidence: 91%
“…1,11 Depending upon the level of amputation, the transected nerves typically have large axonal diameters with mixed sensory and motor fascicles. Symptomatic neuroma has primarily been investigated in the trauma population, with rates of 4 to 48% 19 and with a rate varying based on mechanism -a Turkish study of military personnel showed land-mine injuries having significantly higher rates of neuroma than other trauma necessitating amputations. 20 A subset of neuromatous pain is phantom limb pain or pain perceived in a region of the body that is no longer there.…”
Section: Neuromatous Painmentioning
confidence: 99%
“…Pharmacological treatments have included pain relievers such as nonsteroidal anti-inflammatory medications, opioids, serotonin reuptake inhibitors, tricyclic antidepressants, botulinum, anticonvulsants, NMDA (N-methyl D-aspartate) receptor antagonists, β-blockers, calcium channel blockers, and local anesthetic nerve blocks. 19,21 A recent Cochrane review showed that though some medications showed analgesics effects (morphine, ketamine, dextromethorphan, gabapentin), many had significant side effects, and most studies were limited by small sample sizes and/or bias. 25 Psychological treatments have included mirror therapy, biofeedback, relaxation techniques, and hypnosis.…”
Section: Treatment Of Chronic and Phantom Painmentioning
confidence: 99%
“…In the current analysis, reasons for amputations (traumatic vs nontraumatic) were not associated with incidence estimates in the meta-regression model. It was hypothesized that traumatic amputees recover faster, use prosthesis more, 23 and were, therefore, more likely to detect neuroma pain in the residual limb, 10,22 whereas amputees due to vascular issues were older, with comorbidities, less active, and less likely to complain about issues related to a painful neuroma 10 . The null association between reasons of amputation and incidence of symptomatic neuroma observed in our study is consistent with the findings of a retrospective cohort study, where the incidence of symptomatic neuroma was comparable between traumatic amputees (2/32) and nontraumatic amputees (2/64) ( P = 0.59) 10 …”
Section: Discussionmentioning
confidence: 99%
“…Published incidence of symptomatic neuromata varies widely, with 4% to 49% after lower-limb amputations, 10,11 25% to 26% after upper-limb amputations, 12,13 and 7%% to 8% after finger amputations 14,15 . Studies of incidence of symptomatic neuromata have been limited by small sample sizes and difficulties with the diagnosis because clinical findings are often nonspecific.…”
mentioning
confidence: 99%